The influence of traditional Iranian and Chinese medicine on western and islamic countries - Shahrajabian, Mohamad Hesam; Sun, Wenli; Cheng, Qi (Asian Journal of Medical and Biological Research, 2019)
Traditional Chinese and Iranian medicine are ancient medical and health care systems that still forms an important part of diagnosis and treatment systems in Iran, China and other parts of the world. The integration of these two systems and modern biomedicine is also an important issue. Iranian and Chinese traditional medicines recommended for health promotion and well-being. Chinese herbal drugs have been described by medieval Muslim medical scholars such as Tabari, Rhazes, Haly Abbas, Avicenna and Jurjani (1137 CE). Traditional Chinese and Iranian medicine play an important role in sustainable agriculture and food systems, it also offers a holistic approach to prevent diseases while making appropriate use of organic and herbal products especially growth by small-scale family farmers. Both Iranian and Chinese traditional medicines may help to balance temperature, and both can be health prevention and preservation. Traditional healing practices consist of Islamic religious text based practices, Islamic worship practices and folk healing practices, Islamic religious text based practices are included spiritual healing, medicinal herbs, applied therapy and dietary prescriptions. At present, herbal medications or related products in the global market are derived from Chinese herbs, Indian herbs, Iranian herbs, Arabic herbs, and Western herbs. Herbal remedies may also be classified into three categories, namely, modern herbs, theoretical herbs, and empirical herbs, in accordance with their nature/characteristics and the nature of current usage. Traditional Chinese Asian J. Med. Biol. Res. June 2019, 5(2): 94-99